Analysis of blood lipid changes and influencing factors in physical examination population of a city in central China - Zhu, Boya; Wang, Wenjing; Li, Mengying; Peng, Shuzhen; Tan, Xiaodong (Frontiers in Cardiovascular Medicine, 2022)
Purpose: The prevalence of cardiovascular diseases associated with lipid levels is increasing worldwide. Our purpose is to analyze the distribution level and influencing factors of lipid in the whole population and to put forward suggestions for preventing abnormal lipid levels. Methods: The study was based on a sample of 91480 Chinese who participated in a nationwide physical examination program in Wuhan, a midland city in China, in 2018. The distribution of blood lipid in the population was observed using average, and the relationship between the influencing factors and blood lipid level was observed by quantile regression (QR). Results: A total of 91480 people were evaluated in this study, among which 59165(64.68%) were female with a mean age of 51.71±10.82 years. Quantile regression results showed that different physical examination indexes had different effects on lipid levels. Fasting plasma glucose (FBG) has the largest quantile regression coefficient and BMI had positive effects on total cholesterol (TC), triglyceride (TG), and low-density lipoprotein cholesterol (LDL-C). In males, age has a positive influence on TC, LDL-C, and high-density lipoprotein cholesterol (HDL-C), while in females, age has a positive influence on all four indexes. Conclusions: We found that the TC and LDL-C levels of females were more susceptible to age than males, and the lipid levels of older females were higher than males. BMI has a greater effect on lipid levels in males than in females. Regardless of gender should pay attention to dyslipidemia caused by diabetes and abnormal liver function.